A Somatic Mutation-Derived LncRNA Signature of Genomic Instability Predicts Prognosis for Patients With Liver Cancer - Guo, Cheng; Zhou, Jie; Ma, Boyu; Wang, Rui; Ge, Yanli; Wang, Zhe; Ji, Bing; Wang, Wei; Zhang, Junjie; Wang, Zhirong (Frontiers in Surgery, 2021)
Genome instability is considered one of the hallmarks of Hepatocellular carcinoma (HCC) and brings great challenges to clinical treatment. Emerging evidence revealed the roles of the long non-coding RNA (lncRNA) in genome instability maintaining. Here, we aimed to develop a signature comprised of genome instability-related lncRNAs for prognosis forecast and immunotherapy guidance. Bioinformatics analysis was used to construct the somatic mutation-derived LncRNA signature of genomic instability. HCC patients were stratified into high- and low- risk groups with significant different survival based on the median score of the signature as a cutoff value. Besides, the genome instability-associated lncRNA model was proved to be an independent risk element for HCC patients. Moreover, according to the receiver operating feature (ROC) curve, nomogram and calibration plot, the signature could precisely forecast the survival rate for HCC patients at the first, third and fifth year. Further ssGSEA program revealed the potential capacity for guiding clinical treatment.